2009
DOI: 10.1016/j.pmrj.2009.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lumbosacral Transforaminal Epidural Steroid Injections: A Systematic Review

Abstract: There is fair evidence supporting TFESIs as superior to placebo for treating radicular symptoms. There is good evidence that TFESIs should be used as a surgery-sparing intervention, and that TFESIs are superior to interlaminar ESIs (ILESIs) and caudal ESIs for radicular pain. In patients with subacute or chronic radicular symptoms, there is good evidence that a single TFESI has similar efficacy as a single transforaminal injection of bupivacaine or saline. Future studies should address the ideal number of inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 46 publications
(86 reference statements)
3
88
1
3
Order By: Relevance
“…Many centres combine local anaesthetic and periradicular steroid injections in order to gain both diagnostic information and, potentially, longerterm pain relief for the patient. Evidence collated in SRs 31,77 confirms that transforaminal epidural steroid injections can be a clinically effective and cost-effective part of a management strategy for patients with radicular pain.…”
Section: Unanswered Questions and Future Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Many centres combine local anaesthetic and periradicular steroid injections in order to gain both diagnostic information and, potentially, longerterm pain relief for the patient. Evidence collated in SRs 31,77 confirms that transforaminal epidural steroid injections can be a clinically effective and cost-effective part of a management strategy for patients with radicular pain.…”
Section: Unanswered Questions and Future Researchmentioning
confidence: 98%
“…30 A SR of the topic, conducted in 2009, including nine RCTs, concluded that there is fair evidence that transforaminal epidural steroid injections are superior to placebo for treating radicular symptoms and good evidence that these injections can be used to avoid surgery. 31 However, the independent role of the anaesthetic and the steroid in this overall treatment effect is less clear. A double-blinded RCT comparing up to four nerve root injections using either anaesthetic alone (1 ml of 0.25% bupivacaine) or anaesthetic plus steroid [1 ml betamethasone (6 mg/ml)] in 55 patients with lumbar radicular pain found that the addition of betamethasone increased the proportion of patients deciding not to have surgery from 33% to 71% (p < 0.01).…”
Section: Diagnostic Selective Nerve Root Blocksmentioning
confidence: 99%
“…25 In a systematic review, Roberts et al concluded that there was fair evidence supporting transforaminal epidural injections as superior to placebo for treating radicular symptoms, whereas there was good evidence that they should be used as a surgery-sparing intervention, and that they were superior to interlaminar ESIs and caudal ESIs for radicular pain. 26 Rho and Tang, in an evaluation of the efficacy of lumbar epidural steroid injections, concluded that there was strong evidence to support the use of lumbar transforaminal ESIs in patients with acute to sub acute unilateral radicular pain caused by a herniated nucleus pulposus or spinal stenosis. 27 They also concluded that a lumbar transforaminal epidural steroid injection is an effective surgery-sparing procedure that should be a part of conservative care in the management of LBP and radiculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Transforaminal epidural steroid injections (TFESI) are minimally invasive and safe for treating lumbar radiating pain, and it's popularity is growing among physicians [1]. Many studies demonstrated effectiveness of the TFESIs in managing lumbar radiating pain [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated effectiveness of the TFESIs in managing lumbar radiating pain [1,2]. It is reported that 50-75% of patients with lumbar radiating pain had temporary relief after TFESI.…”
Section: Introductionmentioning
confidence: 99%